Analysis of the characteristics and distribution of types of headaches reported on social media - Dellamonica, Bruna; Peres, Mario (Headache Medicine, 2024)
Introduction The diagnosis of headaches is primarily based on clinical characteristics reported by patients regarding the occurrence of their headaches. There is an inherent bias that depends on the patient's ability to verbally report their experience and the doctor's ability to extract this information during the clinical history. With the growing presence of society on social media, those who suffer from headaches share their experiences, but few studies have been conducted using this data. Objective To explore the use of social media as a data source for analyzing how patients describe their headaches. Methodology The diversity of nomenclatures used by users in an Instagram post was evaluated, where followers were asked to describe in the comments section the type of pain they felt. The data were collected and entered into a spreadsheet, anonymized. A descriptive analysis of the various words used was conducted. Results 175 comments were identified, of which the reports from 129 individuals were considered for analysis. Despite being asked to describe the type and characteristics of their pain, users reported other characteristics not asked about, such as intensity and location. A total of 58 different words were observed to describe the type of pain. The most common were throbbing (12%), pulsating (7%), pressure (6%), constant (5%), and continuous (5%). 70% reported more than one word or phrase to describe their headache experience. Conclusion Understanding the terminology used to describe the types of headaches reported by patients is crucial for effective diagnosis and treatment.